Giardiasis in a patient undergoing chemotherapy for retinoblastoma and acute myelogenous leukemia. Issue 4 (5th August 2013) - Otsubo, Keisuke; Sakaki‐Nakatsubo, Hisano; Taneichi, Hiromichi; Nomura, Keiko; Miyawaki, Toshio; Tokoro, Masaharu; Kanegane, Hirokazu
Abstract: Giardiasis is a common cause of diarrhea in undeveloped countries, but is very rare in developed countries. A patient with acute myelogenous leukemia and retinoblastoma presented with a high fever and severe watery diarrhea during induction chemotherapy. On microscopy, cysts were seen in her stool, suggesting Giardia intestinalis, which was confirmed on polymerase chain reaction (PCR). G. intestinalis was also detected in the patient's asymptomatic parents, who may have transmitted it to the patient. Giardiasis should be tested for in patients with severe and persistent diarrhea during chemotherapy, when other etiologies have been excluded. PCR used to amplify the DNA of G. intestinalis is rapid and sensitive.